Work Readiness pada Mahasiswa Tingkat Akhir: Tinjauan Sistematis terhadap Faktor Penyebab dan Dampaknya - Tria Setyowati (CV. ITTC INDONESIA, 2026)
Work readiness is a key indicator of final-year students' preparedness to enter the workforce amid rapid changes driven by globalization, digital transformation, and the advancement of Artificial Intelligence (AI). These changes require graduates to possess not only academic competencies but also psychological readiness, adaptability, and professional competencies that meet industry demands. This study aims to identify, evaluate, and synthesize research findings on the factors influencing work readiness and its outcomes among final-year university students. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was retrieved from Google Scholar, ScienceDirect, and ERIC, and the selected studies were screened based on predefined inclusion and exclusion criteria. The methodological quality of the included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, and the findings were synthesized using a narrative synthesis approach. A total of 30 articles published between 2020 and 2026 met the eligibility criteria for inclusion. The findings indicate that work readiness is influenced by the interaction of both internal and external factors. The most consistent internal factors include self-efficacy, career adaptability, psychological capital, grit, adversity quotient, and locus of control, while the primary external factors include internship experience, industrial work practice, Work-Integrated Learning (WIL), the Merdeka Belajar–Kampus Merdeka (MBKM/MSIB) program, and digital competencies. Higher levels of work readiness are associated with improved graduate employability, smoother transition from higher education to the workplace, better organizational adaptation, and greater employment opportunities. Overall, work readiness is a multidimensional construct shaped by the interaction of psychological characteristics, professional competencies, learning experiences, and educational support. Therefore, higher education institutions should implement learning strategies that integrate technical competencies, psychological resource development, authentic learning experiences, and digital competencies to better prepare graduates for the evolving demands of the future workforce.